Conexão com a marca ou afinidade com o país? Influências na intenção de compra de marcas dos estados unidos - Moraes, Sergio Garrido (2012)
The purpose of this study is to assess what would have greater impact on purchase intention of products from one country: those aspects of the country, widely researched topic in international marketing, or those aspects of the brand, whose relevance has been pointed out by authors as Samiee, Usunier and Diamantopoulos, sometimes to the detriment of the very concept of country-of-origin. To achieve this goal, the literature review indicated the constructs of country image and country affinity as relevant to assessing the impact of the country. To assess the impact of the brand, the indicated constructs were brand personality and self-brand connection. These constructs can be classified as predominantly affective (affinity and connection) and cognitive (image and personality). As the country to be evaluated, the United States was chosen because it is the source of most valuable brands in the world, and many of them bring to the construction of their identity aspects of American culture. The selected brands were Apple, Levi's and McDonald's, all of high penetration in the studied segment (youngsters), and in evidence both in the economic and cultural fields (high sales, high value, and trendsetters), as in the academic and political scenario (articles, books, anti-American demonstrations). The methodology consisted of a survey conducted with 367 university students from São Paulo, which is also characterized as the target of the brands studied. Data analysis was performed by using the structural equation model, for which they were tested causal relationships between constructs relating to the country and brand with the purchase intention of these brands. The results showed a greater influence on purchase intention of predominantly affective constructs, and among these, the construct of self-brand connection was especially strong and significant. Constructs studied in traditional marketing such as brand personality and image of the country did not result in significant impacts on purchase intentions. These results, however, may vary in intensity depending on the brand. Thus, the paper concludes by stating that the brand, especially those of high brand-equity, would have greater force in the determination of purchase intent than the constructs for the country. The research, however, cannot be generalized, since investigated a group non representative of the population, but provides evidence that can be expanded in future studies, like the investigation of brands with weak brand-equity, other countries, other segments of market and other product categories.